Erdoğan's pragmatism and the ascension of AKP in Turkey: Islam and neo‐Ottomanism. (22nd April 2020) - Gontijo, Lorenzo C. B.; Barbosa, Roberson S.
Abstract: This article aimed to analyze the ascension of Justice and Development Party— Adalet ve Kalkınma Partisi (AKP)—in Turkey and its political measures regarding both Islam and the country's Ottoman past, in order to comprehend the party's role in a potential shift of Turkish national identity and in Turkey's relationship with the Middle East. The article does this through a content analysis of decrees, laws, and other measures taken by the AKP that emphasizes its cultural and religious policies, as well as revisiting literature produced about the subject. Analyzing Recep Tayyip Erdoğan's government during his time as Prime Minister (2003–2014), two noteworthy features come to light: its Islamic influence and its so‐called neo‐Ottomanist outlook. However, this article argues that besides an identity‐ and ideology‐based motivation, the AKP had pragmatic intentions in adopting such approaches, aiming to gather support both domestically and regionally.